Cooperative Communications and Networking Technologies and System Design - Hong, Y.-W. Peter; Huang, Wan-Jen.; Kuo, C.-C. Jay.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Cooperative and relay communications have recently become the most widely explored topics in communications, whereby users cooperate in transmitting their messages to the destination, instead of conventional networks which operate independently and compete among each other for channel resources. As the field has progressed, cooperative communications have become a design concept rather than a specific transmission technology. This concept has revolutionized the design of wireless networks, allowing increased coverage, throughput, and transmission reliability even as conventional transmission techniques gradually reach their limits. Cooperative and relay technologies have also made their way toward next generation wireless standards, such as IEEE802.16 (WiMAX) or LTE, and have been incorporated into many modern wireless applications, such as cognitive radio and secret communications. Cooperative Communications and Networking: Technologies and System Design provides a systematic introduction to the fundamental concepts of cooperative communications and relays technology to enable engineers, researchers or graduate students to conduct advanced research and development in this area. The contents of the book can be summarized as follows: Introduces the reader to various cooperation and relay techniques along with a survey of its role in next generation wireless standards Reviews basic wireless communication and MIMO techniques for readers new to this field Presents fundamental cooperative communication and relay techniques for a basic cooperative entity that consists of only two users and a common destination Fundamental limits of cooperative and relay channels are described from the information-theoretic standpoint Describes how cooperative and relay technology can be integrated with other advanced wireless technology, such as OFDM and MIMO Introduces several cross-layer and networking issues that may arise in cooperative networks, including routing, QoS, and security considerations Cooperative Communications and Networking: Technologies and System Design provides researchers, graduate students, and practical engineers with sufficient knowledge of both the background of cooperative communications and networking, and potential research directions.
Review of Wireless Communications and MIMO Techniques -- Two-User Cooperative Transmission Schemes -- Cooperative Transmission Schemes with Multiple Relays -- Fundamental Limits of Cooperative and Relay Network -- Cooperative Communications with Multiple Sources -- Cooperation Relaying in OFDM and MIMO Systems -- Medium Access Control in Cooperative Networks -- Networking and Cross-Layer Issues in Cooperative Networks.
Keywords: Engineering; Computer communication systems; Coding theory; Complexity, Computational; Electrical engineering; Engineering; Communications Engineering, Networks; Engineering, general; Computer Communication Networks; Coding and Information Theory; Complexity; Electronic books